IMPLEMENTASI APLIKASI PUZZLE MENINGKATKAN MINAT SISWA SEKOLAH DASAR DALAM BAHASA INGGRIS - Iman, Finda Destiani; Trisnawati, Trisnawati; Usmanto, Budi (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2018)
Technological developments Puzzle games are used in this modern era. It is good if the children's learning media is changed with learning that uses the game especially computer devices for education that can advance the mindset to be more advanced and competitive useful in the world of education more effectively and make someone more positive thinking in everyday life. The purpose of this research to produce game-based learning applications to develop software-based media learning to make it easier in thinking. This learning media is very well used for elementary school students to help children more widely developed. The stone tool used with Swish maxe4 application of this puzzle game is expected to solve the problem. So when children play this game indirectly to learn, with the hope of the spirit of children to learn will be more encouraged and improve the quality of learning children.